Enhancing Sustainability of Batik MSMES Through Product Innovation and E-Commerce: A Case Study of Seberang Jambi Indonesia - Muazza; Mayasari Markim; Siti Syuhada; Fachruddiansyah Muslim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines the implementation of product innovation and e-commerce strategies in managing batik SMEs using a sustainability industry approach in Seberang, Jambi City. The study aimed to analyze how product innovation and digital marketing can support them, to explore their understanding and implementation of product innovation and e-commerce, as well as the challenges and sustainability outcomes. Data were collected through the following triangulation methods: observations were carried out during visits to batik workshops and SME locations, literature and document reviews relevant, and semi-structured interviews with in-depth Interviews were conducted with selected owners and managers of batik SMEs in Seberang Kota Jambi. The results showed that innovation in batik design, the use of eco-friendly materials, and the development of Jambi-specific motifs increased the market value of batik, strengthened cultural identity, and appealed to environmentally conscious consumers. On the other hand, e-commerce helped SMEs expand their market reach nationally and internationally, allowing them to compete more effectively. However, several challenges remain, including limited capital for innovation, low digital literacy among business owners, and a lack of policy support from the government. These barriers hindered the full adoption of innovation and digital strategies. Theoretically, this research contributed by enriching the concept of product innovation with a cultural and sustainability-based perspective, expanding the application of e-commerce theory to traditional MSMEs, and reinforcing sustainability theory in the creative industries rooted in local heritage. Moreover, it introduced a new managerial model that integrated local cultural values with modern digital business strategies, offering a practical framework for sustainable development in traditional SME sectors.